Helping to save pangolins from extinction - Choo, SW; Sara, P; Challender, DWS (Wiley Open Access, 2022)
Pangolins, widely distributed in Asia and Africa, have been described as the most heavily trafficked wild mammals globally. Following the emergence of COVID-19, researchers suggested that the Sunda pangolin (Manis javanica) may have been the intermediary host of SARS-CoV-2 in a transmission chain from bats to people. Although subsequent studies have shown that this is unlikely, the impact of this association on pangolins is unknown. In this article, we reflect on the potential impacts of this association in the context of critical knowledge gaps that need to be filled to inform pangolin conservation and mitigate the threats the species. face.